AWT020: a novel fusion protein harnessing PD-1 blockade and selective IL-2 Cis-activation for enhanced anti-tumor immunity and diminished toxicity - Ye, Fan; Huang, Jianing; Cheng, Xiaoli; Chen, Shih Chieh; Huang, Fang; Huang, Wen-Chin; Hua, Botong; Li, Ella; Jiang, Jenny; Lin, Hanna; Siegel, Matthew; Liao, Eric; et al. (Frontiers in Immunology, 2025)
BackgroundThe clinical success of the immune checkpoint inhibitor (ICI) targeting programmed cell death protein 1 (PD-1) has revolutionized cancer treatment. However, the full potential of PD-1 blockade therapy remains unrealized, as response rates are still low across many cancer types. Interleukin-2 (IL-2)-based immunotherapies hold promise, as they can stimulate robust T cell expansion and enhance effector function - activities that could synergize potently with PD-1 blockade. Yet, IL-2 therapies also carry a significant drawback: they can trigger severe systemic toxicities and induce immune suppression by expanding regulatory T cells.MethodsTo overcome the challenges of PD-1 blockade and IL-2 therapies while enhancing safety and efficacy, we have engineered a novel fusion protein, AWT020, combining a humanized anti-PD-1 nanobody and an engineered IL-2 mutein (IL-2c). The IL-2c component of AWT020 has been engineered to exhibit no binding to the IL-2 receptor alpha (IL-2Rα) subunit and attenuated affinity for the IL-2 receptor beta and gamma (IL-2Rβγ) complex, aiming to reduce systemic immune cell activation, thereby mitigating the severe toxicity often associated with IL-2 therapies. The anti-PD-1 antibody portion of AWT020 serves a dual purpose: it precisely delivers the IL-2c payload to tumor-infiltrating T cells while blocking the immune-inhibitory signals mediated by the PD-1 pathway.ResultsAWT020 showed significantly enhanced pSTAT5 signaling in PD-1 expressing cells and promoted the proliferation of activated T cells over natural killer (NK) cells. In preclinical studies using both anti-PD-1-sensitive and -resistant mouse tumor models, the mouse surrogate of AWT020 (mAWT020) demonstrated markedly enhanced anti-tumor efficacy compared to an anti-PD-1 antibody, IL-2, or the combination of an anti-PD-1 antibody and IL-2. In addition, the mAWT020 treatment was well-tolerated, with minimal signs of toxicity. Immune profiling revealed that mAWT020 preferentially expands CD8+ T cells within tumors, sparing peripheral T and NK cells. Notably, this selective tumoral T-cell stimulation enables potent tumor-specific T-cell responses, underscoring the molecule’s enhanced efficacy and safety.ConclusionThe AWT020 fusion protein offers a promising novel immunotherapeutic strategy by integrating PD-1 blockade and IL-2 signaling, conferring enhanced anti-tumor activity with reduced toxicity.